Tinjauan Literatur Greenwashing: Peran Board Characteristics dan Political Connection - Reva Dhiya Ulhaq; Vicky Vendy (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Greenwashing has emerged as a major concern in sustainability reporting due to the growing demand for environmental, social, and governance (ESG) transparency. The increasing prevalence of greenwashing practices has encouraged extensive scholarly attention, particularly regarding the role of corporate governance mechanisms in mitigating such behavior. Despite the growing body of literature, findings concerning the influence of board characteristics and political connections on greenwashing remain fragmented and inconclusive. This literature review synthesizes evidence from 16 Scopus-indexed articles published between 2023 and 2025 to map research developments, identify dominant themes, and highlight existing research gaps. Articles were selected through a structured literature search using keywords related to greenwashing, board characteristics, ESG-washing, and political connections. The review indicates that research is concentrated around three major themes: the influence of board characteristics, the role of political connections, and greenwashing measurement using Natural Language Processing (NLP). Most empirical studies report that board gender diversity and board independence contribute to reducing greenwashing practices by strengthening monitoring and accountability mechanisms. In contrast, the impact of political connections remains inconsistent, with evidence showing both mitigating and exacerbating effects on greenwashing. Furthermore, NLP-based approaches have emerged as promising tools for detecting discrepancies between corporate sustainability disclosures and actual environmental performance. The review reveals limited evidence from developing countries and highlights opportunities for future research involving broader geographical contexts, additional governance variables, and more advanced analytical techniques.